#TITLE_ALTERNATIVE# - MELATI , GITTA
In order to run a business, company must have a capital. The capital sources could be gained from internal financing by using company's retained earning, and external financing through debts. But there is company's policy about the capital structure which regulates the proportion in using debt and equity. There is a critical point where companies could not finance their business using debt anymore. However, when they no longer could use debt anymore, they need to search for another external financing. One of another way is by doing Initial Public Offering (IPO). Besides they could get the additional funding from external investor, IPO brings many benefits such as increase the revenue and brand image of the company. But is the new IPO companies could well- performed in term of financial performance? It is interested to be studied whether the new IPO company well performed or not compare to its market. The market is the sector where new IPO companies are in. When the financial performance of new IPO companies similar to its sector, it could be interpreted that company performed normally. There were 111 companies that executed IPO in Indonesia during 2000-2006, because some of them de-listed or there were no data about them, the object of this research is limited to 98 companies. The objectives of this research are to see the financial performance of new IPO companies from the time they conducted IPO until 2007 compare to their sectors. The results from one sample t-test hypothesis testing show that the new IPO companies have similar performance to the old well-established companies in term of profitability ratios, and liquidity ratio (in term of quick ratio). However, there are significant differences between the new IPO with the old well-established companies in term of indebtedness ratio, liquidity ratio (in term of current ratio). Besides that, consumer goods and financial sector are the sectors which follow the Indonesian financial performances. Due to several limitations in doing this research, the recommendation for the next researches is for studying further about this research to get more depth understanding, especially giving explanations based on the macroeconomic condition.